A book that opens up new spaces of knowledge (KULT_online, 2015)
Mirko Gemmel and Margrit Vogt's collection of essays concerning 'libraries in literature' tackles a topic that has been dealt with extensively before; however, by choosing the focus of 'spaces of knowledge', the authors provide new insights. The volume presents a wide range of essays that give a good historical overview of the topic.